NF-κB signaling mediates homeostatic maturation of new T cells - Silva, Ana; Cornish, Georgina; Ley, Steven C.; Seddon, Benedict (Proceedings of the National Academy of Sciences - PNAS, 2014)
Interleukin (IL)-7 is critical for the maintenance of the peripheral T-cell compartment of the adaptive immune system. Our study identifies a role for the Nuclear Factor κ-B (NF-κB) signalling pathway in the control of IL-7 receptor expression by T cells. Following thymic selection, new T cells specifically up-regulate IL-7R even as they leave the thymus, and we reveal that this expression is strictly NF-κB dependent. NF-κB signaling was only required transiently, however, and once fully mature, naive T cells did not require NF-κB signaling to maintain IL-7R expression. Therefore, we reveal a developmental role for NF-κB signaling for the normal maturation and function of new T cells. Interleukin (IL)-7 is critical for the maintenance of the peripheral T-cell compartment of the adaptive immune system. IL-7 receptor α ( IL-7Rα) expression is subject to developmental regulation and new T cells induce expression as they leave the thymus, which is essential for their long-term survival. It is not understood how this expression is regulated. Here, we identify a role for the Nuclear Factor κ-B (NF-κB) signaling pathway in controlling expression of IL-7Rα in new T cells. Perturbations to NF-κB signaling, either by deletion of Inhibitor of Kappa-B Kinase-2 (IKK2) or by inhibiting Rel dimer activity, prevented normal IL-7Rα expression in new T cells. Defective IL-7Rα expression resulted in impaired survival and homeostatic cell division responses by T cells that could be attributed to their failure to express IL-7Rα normally. Surprisingly, NF-κB signaling was only required transiently in new T cells to allow their normal expression of IL-7Rα, because IKK2 deletion in mature T cells had no effect on IL-7Rα expression or their normal homeostatic responsiveness. Therefore, we identify a developmental function for NF-κB signaling in the homeostatic maturation of new T cells, by regulating IL-7Rα expression.